2019
DOI: 10.3390/nu11020307
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nutritional Factors with Hearing Loss

Abstract: Hearing loss (HL) is a major public health problem. Nutritional factors can affect a variety of diseases, such as HL, in humans. Thus far, several studies have evaluated the association between nutrition and hearing. These studies found that the incidence of HL was increased with the lack of single micro-nutrients such as vitamins A, B, C, D and E, and zinc, magnesium, selenium, iron and iodine. Higher carbohydrate, fat, and cholesterol intake, or lower protein intake, by individuals corresponded to poorer hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 94 publications
0
47
1
6
Order By: Relevance
“…We cannot rule out the possibility that the level of retinol and β-carotene intake was not high, so a significant association could have been observed only in units of weight as RE. In contrast to previous reports, our study found no significant association between PTAs and other dietary antioxidants, such as vitamins B and C [ 24 , 67 ]. Antioxidants may be most effective when working together with other nutrients, but our multivariable model did not include other nutrients, such as vitamin B-12 and E, folate, and magnesium.…”
Section: Discussioncontrasting
confidence: 99%
“…We cannot rule out the possibility that the level of retinol and β-carotene intake was not high, so a significant association could have been observed only in units of weight as RE. In contrast to previous reports, our study found no significant association between PTAs and other dietary antioxidants, such as vitamins B and C [ 24 , 67 ]. Antioxidants may be most effective when working together with other nutrients, but our multivariable model did not include other nutrients, such as vitamin B-12 and E, folate, and magnesium.…”
Section: Discussioncontrasting
confidence: 99%
“…It is well known that systemic inflammation could be decreased or increased by the consumption of peculiar foods [14] and by specific dietary patterns [15]. Anti-inflammatory foods rich in Vitamin A, C, and E like vegetables, fresh fruits and nuts has been considered to be the most important foods protective of ARHL [16]. Likewise, pro-inflammatory foods, like sugar-rich juices, desserts and alcoholic drinks have been shown to increase the risk of onset of ARHL [17].…”
Section: Introductionmentioning
confidence: 99%
“…Patients and clinicians have concerns regarding the effect of diet on hearing loss and tinnitus [13,14]. Therefore, efforts to identify foods that protect hearing are needed.…”
Section: Introductionmentioning
confidence: 99%